Imperfect Markets through Lack of Knowledge - Ozga, S. A. (Quarterly Journal of Economics, 1960)
Some general principles of the diffusion of knowledge, 29. — A single firm, 36. — Imperfect perfect competition, 43. — Conclusions and qualifications, 50.